FDI to the UK will remain robust post-Brexit - Laza Kekic (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2017)
The UK's expected departure from the EU has led to predictions of a negative impact on inward FDI. Strong economic performance and FDI inflows have confounded short-term expectations. The UK's traditional location advantages, business survey results and appropriate government policies suggest that FDI will remain robust in the long term.
Keywords: 330